Faktor Yang Mempengaruhi Kejadian Diare Di Tambak Sari Kota Surabaya - Debby Daviani Prawati (Universitas Airlangga, 2019)
Background: Diarrhea is an illness which characterized by changed in shape, consistency of the stool and with excessive bowel frequency (more than 3 times within a day). Diarrhea disease is the third contributor of children's morbidity and mortality rate around the world. Purpose: This study aims to analyzing factors that caused diarrhea's cases. This research were an observational analytic type. Sampling technique were used random sampling / probability sampling. Methods: Data were analyzed by chi-square test. Data collection techniques were divided into primary data (direct observation and questionnaire) and secondary data (journals and articles). Results: On this research showed theres no significant correlation between sex, age, education, income, hand washing behavior using soap, clean water facility and trashbin condition with diarrhea occurrence during last 3 months in RW.VI Kelurahan Rangkah Buntu, Surabaya. There were a significant relation between cleaning up the environment, making and consuming oralit, and the behavior of handwashing with soap before meals at the rate of diarrhea cases during the last 3 months in RW VI Kelurahan Rangkah Buntu, Surabaya. Conclusion: theres no significant correlation between social demography, behavior using soap, clean water facility and trasbin and a significant relation between clean up the environtment, behavior handwashing, making and consuming oralit during the last 3 month in RW VI Kelurahan Rangkah Buntu, Surabaya.